Art of publication and selection of journal - Ashish Singh; Shweta Singh; P Mercy; Ajai Kumar Singh; Deepti Singh; Manish Singh; Pratibha Singh (Wolters Kluwer Medknow Publications, 2014)
Publication is both an art and a science. For the beginner, not knowing the intricacies of publication, choice of subject and the appropriate journal to get their work published are major obstacles. In this article, the authors share their experience on how to go about getting an article published and selecting the most suitable journal for publication. They hope this article stimulates medical writing.